Authentic industry-based role-play for improving hospitality students’ oral communication and learning engagement: An experiment - Suparmi, Suparmi; Alhusna, Asma; Christina, Dian; wahyuni, Irma (Journal of English Language Teaching Innovations and Materials (Jeltim), 2026)
Despite the importance of hospitality expressions for professional service encounters, many vocational students struggle to use them appropriately due to limited opportunities for authentic communicative practice. This study aims to examine the effectiveness of authentic industry-based role-play in enhancing tourism students’ oral communication and learning engagement in Hospitality English classes. A quasi-experimental one-group pretest–posttest design was employed involving 32 eleventh-grade tourism students. Data were collected through a speaking test and a questionnaire, and the intervention was conducted in six meetings with authentic role-play based on real hotel scenarios. The data were analyzed using descriptive statistics and paired-sample t-tests. The results show that students’ oral English communication improved before and after the intervention. The improvement was shown in students’ speaking scores from the pre-test (M = 62.81) to the post-test (M = 81.34) and the paired-sample t-test (t(31) = -12.47 and a very large effect size p < .001, d = 2.20), suggesting that authentic industry-based role-play had a substantial impact on students’ speaking performance. Furthermore, students demonstrated a high level of learning engagement throughout the intervention, as reflected by a mean score of 4.36 (strongly high), indicating active participation, enthusiasm, and sustained involvement in classroom activities. The finding suggests that integrating authentic, workplace-oriented communicative tasks can effectively enhance students’ communicative competence, offering practical implications for ESP pedagogy, particularly in vocational hospitality education.